2019
DOI: 10.1111/jan.14008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pressure injury among Chinese community‐dwelling older people and its risk factors: A national survey based on Chinese Longitudinal Healthy Longevity Survey

Abstract: Aim To investigate the distribution of pressure injuries among older adults in China and to identify the associated risk factors. Design Cross‐sectional study. Methods The identified subjects were collected from 2012 wave of a national Chinese Longitudinal Healthy Longevity Survey. Older people were defined as being 65 years of age or older. We used chi‐square test and binary logistic regression to investigate the risk factors of pressure injury development. Results A total of 55 older people were documented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Similar to the incidence rate in our study of 45% (n=62), an earlier UK study with a smaller sample of community dwelling patients reported 51% (n=17) of PI were community acquired. 40 Whereas an Australian study reported 40.8% of identified PI developed during care by community nursing services, with nearly 70% of the PI being caused by devices such as shower chairs 41. A Chinese study found a lower prevalence of PI in community dwelling older people 42 , however these patients self-reported PI and in another publication we have shown poor recognition of PI's by patients who often fail to recognise PI or understand risk factors. 43 (blinded for peer review)…”
Section: Discussionmentioning
confidence: 59%
“…Similar to the incidence rate in our study of 45% (n=62), an earlier UK study with a smaller sample of community dwelling patients reported 51% (n=17) of PI were community acquired. 40 Whereas an Australian study reported 40.8% of identified PI developed during care by community nursing services, with nearly 70% of the PI being caused by devices such as shower chairs 41. A Chinese study found a lower prevalence of PI in community dwelling older people 42 , however these patients self-reported PI and in another publication we have shown poor recognition of PI's by patients who often fail to recognise PI or understand risk factors. 43 (blinded for peer review)…”
Section: Discussionmentioning
confidence: 59%
“…In nursing homes and hospitals in Germany, more women were underweight and at pressure injury risk 13 . Among Chinese community–dwelling older people, pressure injury was shown to be associated with age, disability, incontinence, cancer, and dementia 14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Among Chinese community-dwelling older people, pressure injury was shown to be associated with age, disability, incontinence, cancer, and dementia. 14 The sacrum is the most common site of acquired pressure injury in all patients (both critically ill and noncritically ill). 9 Most damage occurring to the sacrum is attributed to pressure, shear, excessive moisture, or a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Agency for Healthcare Research & Quality (AHRQ), nearly 2.5 million people are affected by PI, and more than 60,000 patients in the United States die directly from PI each year 2 . In patients who are weak, elderly, bedridden, malnourished, prone positioning, and unable to take care of themselves, especially critically ill, the incidence of PI is high 3–5 …”
Section: Introductionmentioning
confidence: 99%